Analisis Kesuksesan Sistem Informasi Manajemen Puskesmas pada Pengelolaan Obat di Puskesmas Kabupaten Batang - Rizza Fauziyah; Satibi Satibi; Eko Nugroho (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Every Public Health Center in all regions of Batang Regency has implemented a Public Health Center Management Information Systems (SIMPUS) in drug management since 2010 to accelerate access to the drug data, accelerate and improve the accuracy of prescription services, as well as provide accurate and timely information to support the planning, supply, and distribution processes. This study aims to analyze the level of success in the use of information management systems for drug management in the Batang District public health center in terms of user perceptions. This research is a descriptive quantitative analytic. The data from 29 respondents were collected using a questionnaire survey developed from the updated Delone and McLean success model. The quantitative analysis of the questionnaire uses a "Likert" attitude scale. Hypothesis testing is done to find out how the relationship and influence between variables using Structural Equation Modeling Partial Least Square (SEM-PLS) analysis. Hypothesis testing used two-way probability with a significance level (α) of 5%, whereas the T-statistic value is more than 1.96, which means there is a significant influence between variables. The results showed that the relationship of system quality variable on system use, system quality on user satisfaction, and service quality on user satisfaction has a positive but not significant effect. The relationship of system use variables to user satisfaction has a negative and not significant effect. While the relationship between variable information quality on system use, information quality on user satisfaction, service quality on system use, system use on net benefit, and user satisfaction on net benefit has a positive and significant effect. It can be stated that the success of SIMPUS utilization as a whole in drug management in the Batang District Public Health Center is not optimal, it needs an improvement on the reliability and effectiveness of the system and the service quality to increase the level of utilization.